Recommendations for Healthy Nutrition in Female Endurance Runners: An Update - Deldicque, Louise; Francaux, Marc (Frontiers in Nutrition, 2015)
The purpose of this review is to present the basic principles of a healthy nutrition in female endurance runner enriched by the latest scientific recommendations. Female endurance runners are a specific population of athletes who need to take specifically care of daily nutrition due to the high load of training and the necessity to keep a rather low body mass. This paradoxical situation can create some nutritional imbalances and deficiencies. Female endurance athletes should pay attention to their total energy intake, which is often lower than their energy requirement. The minimal energy requirement has been set to 45kcal/kg fat free mass/day plus the amount of energy needed for physical activity. The usual recommended amount of 1.2-1.4g protein/kg/day has recently been questioned by new findings suggesting that 1.6g/kg/day would be more appropriate for female athletes. Although a bit less sensitive to carbohydrate loading than their male counterparts, female athletes can benefit from this nutritional strategy before a race if the amount of carbohydrates reaches 8g/kg/day and if their daily total energy intake is sufficient. A poor iron status is a common issue in female endurance runners but iron-enriched food as well as iron supplementation may help to counterbalance this poor status. Finally, they should also be aware that they may be at risk for low calcium and vitamin D levels.